Śuklayajurvedīnām āhnikakarmma- sūtrāvaliḥ - Sharma, S. D. (Shive Datta), 1933- (Lakshmivenṅkaṭeśvara Sṭīm-Presa, 1983)
Manual of Hindu daily rites, presenting Mādhyandina recension of the Vājasaneyisaṃhitā of Yajurveda.